Hypertension treatment practices and its determinants among ambulatory patients: retrospective cohort study in Ethiopia. Issue 8 (3rd August 2017) - Berhe, Derbew Fikadu; Taxis, Katja; Haaijer-Ruskamp, Flora M; Mulugeta, Afework; Mengistu, Yewondwossen Tadesse; Mol, Peter G M
Abstract : Objectives: We examined determinants of achieving blood pressure control in patients with hypertension and of treatment intensification in patients with uncontrolled blood pressure (BP). Design: A retrospective cohort study in six public hospitals, Ethiopia. Participants: Adult ambulatory patients with hypertension and with at least one previously prescribed antihypertensive medication in the study hospital. Outcome: Controlled BP (<140/90 mm Hg) and treatment intensification of patients with uncontrolled BP. Results: The study population comprised 897 patients. Their mean age was 57 (SD 14) years, 63% were females, and 35% had one or more cardiometabolic comorbidities mainly diabetes mellitus. BP was controlled in 37% of patients. Treatment was intensified for 23% patients with uncontrolled BP. In multivariable (logistic regression) analysis, determinants positively associated with controlled BP were treatment at general hospitals (OR 1.89, 95% CI 1.26 to 2.83) compared with specialised hospitals and longer treatment duration (OR 1.04, 95% CI 1.01 to 1.06). Negatively associated determinants were previously uncontrolled BP (OR 0.30, 95% CI 0.21 to 0.43), treatment regimens with diuretics (OR 0.68, 95% CI 0.50 to 0.94) and age (OR 0.99, 95% CI 0.98 to 1.00). The only significant—positive—determinant for treatment intensification was duration of therapy (OR 1.05, 95% CI 1.02 to 1.09). Conclusions: The level of controlled BP and treatment intensification practice in this study was low. The findings suggest the need for in-depth understanding and interventions of the identified determinants such as uncontrolled BP on consecutive visits, older age and type of hospital.